Μακεδονικά Επιγραφικά IV (Θεσσαλονίκη) - Νίγδελης, Παντελής Μ. (Tekmeria, 2013)
This article contains corrections, restorations and comments concerning various inscriptions of Thessaloniki and its territory that appeared in dispersed publications following Ch. Edson’s edition of IG X 2.1 (Inscriptiones Thessalonicae et viciniae) in 1972.